Social housing plans of peronist government in mar del plata city, argentina, 1946-1955 (2010)
This text presents an analysis of housing and its social spaces in relation to the production of typological and technological formal alternatives that are a vulnerable heritage at Mar del Plata, housing built between 1946 and 1955 by the Peronist government. The Peronist government intervention in relation to public housing was not restricted to physical dimension; it also redefined social relationships and political spaces. In those housing complexes the essential concerns where, among others, the access to a good quality of life and its integration to the city and its equipments.